Autonomous Camera Tracking System Using Image Processing for Dynamic Educational Content Creation - Solakhudin, Muhammad Rafi; Sinka, Valina; Gunawan, Sri; Mustajib, Muhammad (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2025)
In the context of the Online Learning activity, where video content plays a crucial role in educational materials, the demand for effective video production systems has become essential. Traditionally, at least two people are needed to operate cameras, which poses a challenge due to limited human resources. This study addresses this issue by developing a Camera Position Tracking System using image processing, specifically utilizing the MediaPipe framework for real-time tracking of presenters. The system's mechanics enable a DSLR camera to automatically adjust its position based on the presenter’s movement, detected within a range of 1.5 to 8 meters. The light intensity required for optimal operation is between 125 and 190 lux. The system's success lies in converting detected position data into motor stepper pulses that move the camera, ensuring efficient, cost-effective video production with minimal human intervention.